Strengthening Bangladesh's Public Service Commission - World Bank (Washington, DC, 2013)
Bangladesh's Public Service Commission (PSC) is a constitutionally mandated custodian of merit-based recruitment to the civil service. In practice, however, it is perceived to be a weak organization that has not always well-managed the recruitment process. Since the 1990s the media has reported politicized appointment of its members. Recently there have been allegations of examination irregularities, including leakage of question papers of the civil service examinations. The management of the PSC and its role in civil service recruitment has departed from comparative administrative practice. This note argues that the PSC's independence from micromanagement by the executive, and its improved management of the civil service examination are critical for its credibility to uphold the merit principle. It lists short- and medium-term actions that could help in restoring the PSC's intended role and functions. PSCs are common in administrative traditions where the appointed executive is meant to be permanent, politically neutral and unaligned to any particular political party or group of elected officials. A PSC forms a critical piece of the public sector's good governance framework by providing a check and balance between the government's interest and its employee's interests. In recruitment, which is an important element of civil service management, the PSC protects the government's interest by selecting the best among available candidates for a particular position.